2016
DOI: 10.35790/ebm.4.1.2016.10838
|View full text |Cite
|
Sign up to set email alerts
|

Infeksi parasit usus pada anak sekolah dasar di pesisir pantai Kecamatan Wori Kabupaten Minahasa Utara

Abstract: Parasite infection is still an endemic disease that can be found in any place in Indonesiathat can cause problems in public health, especially for children in elementary school age. The purpose of this research is to describe the intestinal parasite infection in children at coastal area in Wori district, North Minahasa regency. The method of this research is descriptive survey. The subject of this research is student class I to VI of GMIM Budo and Kima Bajo elementary school in Wori district.The result of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 2 publications
0
2
1
9
Order By: Relevance
“…[18] The parasites found in this study were dominated by Ascaris lumbricoides (38.5%), Trichuris trichiura (11.5%), hookworm (11.5%), and Blastocystis hominis (11.5%). However, different results from the widest parasites found in the study, reported by Tangel et al, [19] i.e., ≥50 eggs/10 ml of urine). The prevalences of the pathogenic intestinal protozoa G.…”
Section: Discussioncontrasting
confidence: 62%
“…[18] The parasites found in this study were dominated by Ascaris lumbricoides (38.5%), Trichuris trichiura (11.5%), hookworm (11.5%), and Blastocystis hominis (11.5%). However, different results from the widest parasites found in the study, reported by Tangel et al, [19] i.e., ≥50 eggs/10 ml of urine). The prevalences of the pathogenic intestinal protozoa G.…”
Section: Discussioncontrasting
confidence: 62%
“…Berdasarkan penelitian di Daerah Wori, dengan karakteristik tanah yang sama dengan wilayah penelitian yaitu di pesisir pantai memiliki tanah gembur terdiri dari pasir dan humus serta sedikit tanah liat sehingga telur cacing dapat berkembang dengan baik di dalamnya. 21 Akibat infeksi cacing T. trichiura dapat menimbulkan peradangan pada daerah yang ditempeli cacing dan memicu kolitis. Penyakit kolitis yang berkepanjangan dapat menimbulkan gejala klinis nyeri perut dan diare, selain itu penderita dapat mengalami kekurangan gizi dan anemia.…”
Section: Hasil Dan Pembahasanunclassified
“…Another study conducted in coastal area of Wori Sub-district, North Minahasa District showed that 4.7% children suffered from intestinal helminth infections and 15.5% children were infected with with intestinal protozoa. 8 In addition, previous research in coastal area of Makassar City reported that the prevalence of intestinal helminth infections was 59.3% in children. 9 Therefore, the incidence of intestinal parasitic infection is still quite high in Indonesia.…”
Section: Abstrakmentioning
confidence: 97%